User-centered design of online learning communities - Lambropoulos, Niki 1966-.; Zaphiris, Panayiotis; Gale Group (Hershey, Penn. Information Science Pub., 2007)
"This book explains how computers can be used to augment human intellect for productivity and innovation, both nationally and globally."--GVRL description.
"This book is anchored in the concept that information technology empowers and enhances learners' capabilities adopting a learning summit on using the machine for the augmentation of human intellect for productivity, improvement, and innovation at individual, organizational, societal, national, and global levels"--Provided by publisher.
Electronic reproduction.
Keywords: Distance education -- Computer-assisted instruction; Educational technology; User interfaces (Computer systems); Computer software -- Development; Electronic books